2019
DOI: 10.1002/er.4993
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting energy via stimuli‐free water/moisture dissociation by mesoporous SnO 2 –based hydroelectric cell and CuO as a pump for atmospheric moisture

Abstract: Water dissociation, in general, requires external stimuli such as light energy or electricity. Here, we present a stimuli-free water dissociation using mesoporous SnO 2 -based hydroelectric cell that can directly be exploited to generate electric power for portable applications. The device configuration is almost identical to metal-air batteries but follows altogether a different reaction pathway. The mesoporous SnO 2 -based hydroelectric cell dissociates water molecule into hydroxyl ions (OH -) and hydronium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…However, Co‐MOFs as active materials illustrate a pair of obvious oxidation and reduction peaks. This means that Co‐MOFs as active materials show a similar electrochemical reaction process for metal compound such as CuO or SnO 2 33‐35 . Contact current charge and discharge tests show that graphene oxide has a quite high initial discharge specific capacity at various current densities.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…However, Co‐MOFs as active materials illustrate a pair of obvious oxidation and reduction peaks. This means that Co‐MOFs as active materials show a similar electrochemical reaction process for metal compound such as CuO or SnO 2 33‐35 . Contact current charge and discharge tests show that graphene oxide has a quite high initial discharge specific capacity at various current densities.…”
Section: Resultsmentioning
confidence: 88%
“…This means that Co-MOFs as active materials show a similar electrochemical reaction process for metal compound such as CuO or SnO 2 . [33][34][35] Contact current charge and discharge tests show that graphene oxide has a quite high initial discharge specific capacity at various current densities. But the speed of capacity decay is very fast.…”
Section: Electrochemical Mechanism Analysis Of the Electrochemical mentioning
confidence: 99%
“…It results into a continuous flow of electric current and voltage developed in the cell. Till now 12 research papers have been published in SCI peer reviewed international journals by Kotnala et al group and nine from other groups in last 3 years 37‐46 . With further study of base material, the initial key material magnesium ferrite with nominal lithium substitution has been strategically processed and engineered to make it Nano porous and oxygen deficient for water splitting at room temperature.…”
Section: Hydroelectric Cell (Hec)mentioning
confidence: 99%
“…Till now 12 research papers have been published in SCI peer reviewed international journals by Kotnala et al group and nine from other groups in last 3 years. [37][38][39][40][41][42][43][44][45][46] With further study of base material, the initial key material magnesium ferrite with nominal lithium substitution has been strategically processed and engineered to make it Nano porous and oxygen deficient for water splitting at room temperature. Magnesium ferrite is a soft magnetic material (general formula AB 2 O 4 ) and it is highly resistive among all ferrites due to oxygen vacancies.…”
Section: Magnesium Ferrite Based Hecmentioning
confidence: 99%
“…Inspired by these natural phenomena, the uptake of water vapor by various surfaces has become a vibrant research topic. For example, it has been shown that atmospheric water harvesting can be used to produce freshwater, support irrigation systems, or generate electric power. …”
Section: Introductionmentioning
confidence: 99%